THE ROLE AND SIGNIFICANCE OF BIOMECHANICAL APPROACHES IN DEVELOPING THE PHYSICAL PREPAREDNESS OF TAEKWONDO ATHLETES DURING THE TRAINING PROCESS (World Bulletin of Physical Education and Sports Science, 2025)
This article provides a scientific analysis of the role and importance of biomechanical approaches in shaping the physical preparedness of taekwondo athletes during the training process. Biomechanical indicators such as kicking velocity, joint angles of lower limbs, force moments, and body mass distribution are examined in terms of their integration into training methodology. Modern technological tools (motion capture cameras, force platforms, 3D motion analysis) for biomechanical diagnostics are also reviewed. This biomechanical approach offers a scientific foundation for coaches and researchers to enhance the training efficiency of taekwondo practitioners.
Keywords: Taekwondo, biomechanics, physical preparedness, movement technique, striking power, balance, sensor analysis.